(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The objectives of this study were to determine the blending parameters of coconut shell powder (CSP) modified asphalt binder and to evaluate the rheological properties of CSP modified asphalt binder. CSP of 2%, 4%, 6%, 8% and 10% by weight of asphalt have been incorporated into an unaged 80/100 asphalt mix in order to improve its performance. The influence of the additives on the physical and rheological properties was evaluated with penetration test, softening point, storage stability, dynamic shear rheometer test (DSR), and Field Emission Scanning Electron Microscope (FESEM). The aging of asphalt binders was simulated in a laboratory by using Rotational Thin Film Oven (RTFO). The results showed that the addition of CSP into virgin binder was decreasing the penetration value and increasing the softening point temperature compared to the original binder. On the rheological effect, for unaged modified binder, higher CSP resulted higher G*/sin Î´ especially at lower temperature compared to the unaged control binder. Besides, for the aged modified binder, stiffness was lower than the control aged binder for all temperature.